Portrait Of Women In Oscar Wilde's A Woman Of No Importance And George Bernard Shaw's Pygmalion - Slamet, Budiyono; , Dr. Phil. Dewi Candraningrum, M.Ed; , Dr. M. Thoyibi, M.S (2014)
This research aims at: (1) finding out the social class structure of the women characters in Oscar Wilde's A Woman of No Importance and George Bernard Shaw's Pygmalion based on sociological perspective; (2) examining the struggle of the women characters in the Oscar Wilde's A Woman of No Importance and George Bernard Shaw's Pygmalion based on feminist perspective. The qualitative research is carried out by making use of the descriptive method. The researcher analyzes the data by using sociology of literature and feminist approach. The analysis is used for: describing the social class of the women and analyzing the women struggle to fight for the inequality of rights. Based on the result of the data analysis, the research findings are: (1) there are social classes reflected in Oscar Wilde's A Woman of No Importance and George Bernard Shaw's Pygmalion in the Victorian age which brougth misery to the poor people or lower social class; (2) the major female characters did efforts as they seem the inequality of right, role and participation in the society to make their right equal as men. (3) giving the opportunity of equal education to the working class especially for the women will make them have an option to get the same level or in other words there is no social class distinction and gender inequality.